2017
DOI: 10.1002/da.22712
|View full text |Cite
|
Sign up to set email alerts
|

A classical twin study of PTSD symptoms and resilience: Evidence for a single spectrum of vulnerability to traumatic stress

Abstract: Genetic factors contribute to a single spectrum of traumatic stress reflecting resilience at one end and high symptom severity at the other. This carries implications for phenotype refinement in the search for molecular genetic markers of trauma-related psychopathology. Rather than focusing only on genetic risk for PTSD, molecular genetics research may benefit from evaluation of the broader spectrum of traumatic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 41 publications
3
56
2
Order By: Relevance
“…4,5 Exposure to traumatic stress is, by definition, requisite for the development of PTSD, but individual susceptibility to PTSD (conditioned on trauma exposure) varies widely. Twin studies over the past two decades provide persuasive evidence for at least some genetic influence on PTSD risk, 6,7 and the last decade has witnessed the beginnings of a concerted effort to detect specific genetic susceptibility variants for PTSD. [8][9][10][11][12] The Psychiatric Genomics Consortium -PTSD Group (PGC-PTSD) recently published results from the largest GWAS on PTSD to date, involving a transethnic sample of over 20,000 individuals, approximately 25% of whom were cases.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Exposure to traumatic stress is, by definition, requisite for the development of PTSD, but individual susceptibility to PTSD (conditioned on trauma exposure) varies widely. Twin studies over the past two decades provide persuasive evidence for at least some genetic influence on PTSD risk, 6,7 and the last decade has witnessed the beginnings of a concerted effort to detect specific genetic susceptibility variants for PTSD. [8][9][10][11][12] The Psychiatric Genomics Consortium -PTSD Group (PGC-PTSD) recently published results from the largest GWAS on PTSD to date, involving a transethnic sample of over 20,000 individuals, approximately 25% of whom were cases.…”
Section: Introductionmentioning
confidence: 99%
“…Though a growing body of preclinical and translational research is illuminating biological mechanisms of stress resilience (McEwen et al, ), relatively little is known about the genetic basis of psychological resilience in humans (Feder, Horn, Haglund, Southwick, & Charney, ). Twin studies have suggested that self‐ (or parent‐) assessed resilience—defined as a perceived capacity to cope adaptively with stressors—is moderately heritable (~30–50%) (Amstadter, Myers, & Kendler, ; Waaktaar & Torgersen, ; Wolf et al, ). Studies in twin samples and unrelated individuals have also suggested that other traits reflecting positive psychological adjustment, such as subjective well‐being and positive affect are partially heritable (Haworth et al, ; Rietveld et al, ; Wingo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although most Americans (50-85%) experience traumatic events over a lifetime, most do not develop PTSD -lifetime PTSD prevalence is approximately 7% (Kessler and Wang, 2008), suggesting differential resilience to stress and vulnerability to the disorder (Atwoli et al, 2015). There is a substantial heritable basis for PTSD risk (Stein et al, 2002;Wolf et al, 2018), and evidence from genome-wide association studies (GWAS) shows that PTSD, like other mental disorders , is highly polygenic (Benjet et al, 2016;Daskalakis et al, 2018;Duncan et al, 2018;Nievergelt et al, 2018;Xie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%